Dissociable Catecholaminergic Modulation of Visual Attention: Differential Effects of Catechol-O-Methyltransferase and Dopamine Beta-Hydroxylase Genes on Visual Attention. (1st August 2019) - Shalev, Nir; Vangkilde, Signe; Neville, Matt J.; Tunbridge, Elizabeth M.; Nobre, Anna C.; Chechlacz, Magdalena
Abstract: Visual attention enables us to prioritise behaviourally relevant visual information while ignoring distraction. The neural networks supporting attention are modulated by two catecholamines, dopamine and noradrenaline. The current study investigated the effects of single nucleotide polymorphisms in two catecholaminergic genes – COMT (Val 158 Met) and DBH (444 G/A) – on individual differences in attention functions. Participants ( n = 125) were recruited from the Oxford Biobank by genotype-based recall. They were tested on a continuous performance task (sustained attention), a Go/No-Go task (response inhibition), and a task assessing attentional selection in accordance with the Theory of Visual Attention (TVA). We found a significant effect of DBH genotype status on the capacity to maintain attention over time (sustained attention) as measured by the continuous performance task. Furthermore, we demonstrated a significant association between COMT genotype status and effective threshold of visual perception in attentional selection as estimated based on the TVA task performance. No other group differences in attention function were found with respect to the studied genotypes. Overall, our findings provide novel experimental evidence that: (i) dopaminergic and noradrenergic genotypes have dissociable effects on visual attention; (ii) either insufficient or excessive catecholaminergic activity may have equally detrimental effects on sustained attention. Highlights: Catecholaminergic genotypes have dissociative cognitive effects on visual attention. DBH (444 G/A) polymorphism affects sustained attention. COMT Val 158 Met polymorphism affects perceptual threshold in visual attention. Both too little and too much catecholamines may detrimentally impact sustained attention.